Recurrent cholangitis after choledochoduodenostomy: A case report. (March 2022) - Uwuratuw, Julianus Aboyaman; Bakhtiar, Bustaman; Labeda, Ibrahim; Syarifuddin, Erwin; Christeven, Robert; Faruk, Muhammad
Abstract: Introduction: Recurrent cholangitis is a long-term consequence of choledochoduodenostomy (CDD) that requires urgent treatment. The frequency of recurrent cholangitis ranges between 2.5 and 15.7%. This case demonstrated the importance of rapid and precise diagnosis through screening and therapeutic modalities in recurrent cholangitis. Presentation of case: A male patient presented with a history of recurring right upper abdominal discomfort during the previous 3 years. The pain had been intermittent but had become more intense during the prior month. The patient was diagnosed with recurrent cholangitis following CDD. The therapeutic plan was closure of the CDD, which was identified as the cause of the recurrent cholangitis, and biliary drainage by modified Roux-en-Y choledochojejunostomy. Discussion: Recurrent cholangitis was diagnosed based on clinical manifestations, including recurring right upper abdomen discomfort, jaundice, and fever accompanied with consistent laboratory and imaging findings. Drainage of bile into the distal common bile duct (CBD) is reduced in the side-to-side CDD arrangement. Consequently, the distal CBD becomes a reservoir with inadequate drainage, predisposing this so-called 'sump' to debris accumulation and cholangitis. The surgery was considered successful in preventing the recurrent cholangitis. Conclusion: The recurrent cholangitis was occurred due to inadequate biliary drainage. The choledochojejunostomy procedure with modified Roux-en-Y might prevent the recurrent cholangitis by improving biliary drainage to the enteric. Highlights: Recurrent cholangitis in side-to-side CDD may be induced by infection. Recurrent cholangitis manifests with symptoms such as abdominal pain, jaundice, and fever. The principal treatment is to enhance the biliary drainage of the CBD to the anastomosis